OPTIMIZATION OF REACTION TIME IN THE TRANSESTERIFICATION OF DISTILLED-WATER-WASHED USED COOKING OIL INTO FATTY ACID METHYL ESTERS - Talitha Fitra Firdhausya; Yulfi Zetra; R. Y. Perry Burhan; Rizka Berliana Putri; Yunita Alfiyati Firdausa (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2026)
Fatty acid methyl ester (FAME) is an alternative to fossil diesel fuel that can be synthesized from used cooking oil (UCO). UCO requires pretreatment before it can be used for FAME synthesis because of its high acid value. Pretreatment of UCO using distilled-water washing reduced the acid value from 11.80 mg KOH/g to 3.49 mg KOH/g. The treated UCO was reacted with methanol through transesterification at reaction times of 90, 120, 150, and 180 min to produce FAME. The acid value decreased with increasing reaction time, from 1.57 mg KOH/g at 90 min to 0.97 mg KOH/g at 120 min and 0.43 mg KOH/g at 150 min. However, the acid value increased again at 180 min to 1.10 mg KOH/g, which was attributed to the reversible nature of the reaction. The FAME sample with the lowest acid value was analyzed using GC–MS, and five methyl esters were identified: methyl myristate (2.86%), methyl palmitate (65.88%), methyl oleate (19.25%), methyl stearate (10.85%), and methyl arachidate (0.10%), along with other compounds (1.06%). FAME synthesized from UCO pretreated by distilled-water washing has the potential to reduce large-scale FAME production costs because the distilled-water washing process is highly economical.